1981
DOI: 10.1136/ard.40.6.558
|View full text |Cite
|
Sign up to set email alerts
|

A controlled survey of sacroiliitis in Behcet's disease

Abstract: SUMMARY Among 37 patients with Beh9et's disease in Turkey the radiographic presence of sacroiliitis was no more frequent than in 28 age and sex matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 4 publications
0
27
0
4
Order By: Relevance
“…In addition, several patients with coexisting AS and BD have been described in the literature (11,(16)(17)(18)(19). However, other authors have found that the prevalence of AS or SI in BD has not been different from that in the general population (20)(21)(22)(23)(24). Although Dilsen et al reported the highest level of 33 (10%) patients with AS and 112 (34%) with SI among 334 Turkish patients with BD (13), other authors found no evidence of an increased frequency of SI in patients with BD and described only one patient with definitive AS among 114 patients with BD in the same population (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several patients with coexisting AS and BD have been described in the literature (11,(16)(17)(18)(19). However, other authors have found that the prevalence of AS or SI in BD has not been different from that in the general population (20)(21)(22)(23)(24). Although Dilsen et al reported the highest level of 33 (10%) patients with AS and 112 (34%) with SI among 334 Turkish patients with BD (13), other authors found no evidence of an increased frequency of SI in patients with BD and described only one patient with definitive AS among 114 patients with BD in the same population (20).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Etaouil et al, found HLA-B27 positivity and HLA-B51 negativity in 2 cases with combined AS and BD [10]. Yazıcı et al, assessed 184 BD patients in Turkish population and found AS only in 1 case [11]. Yazıcı et al, indicated that the sacroiliac joint antero-posterior assessment differ greatly from person to person, therefore suggested the prevalence of sacroilitis in BD to be unclear [12].…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between HLA phenotypes of Behcet's disease and AS cases was detected in the literature [13]. There is HLA-B27 positivity in approximately 90% of SPA patients and HLA-B5 positivity in 60 to 80% of BD patients [8,11]. Incidence of HLA-B27 is more frequent in patients with co-existing BD and SPA [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…HLA B51 and B27 were more frequently found to be positive in patients with coexisting BD and AS than normal population. Yazıcı et al (4) reported only a single case defined AS among 114 patients with BD. This study showed no relationship between AS and BD.…”
Section: Discussionmentioning
confidence: 99%